Assessment of Behavioral Health Services Use Among Low-Income Medicare Beneficiaries After Reductions in Coinsurance Fees - Fung, Vicki (JAMA Netw Open, 2020)
IMPORTANCE: Medicare has historically imposed higher beneficiary coinsurance for behavioral health services than for medical and surgical care but gradually introduced parity between 2009 and 2014. Although Medicare insures many people with serious mental illness (SMI), there is limited information on the impact of coinsurance parity in this population. OBJECTIVE: To examine the association between coinsurance parity and outpatient behavioral health care use among low-income beneficiaries with SMI. DESIGN, SETTING, AND PARTICIPANTS: This cohort study used Medicare claims data for a 50% national sample of lower-income Medicare beneficiaries from January 1, 2007, to December 31, 2016. The study sample included patients with SMI (schizophrenia, bipolar disorder, or major depressive disorder). Data analysis was performed from August 1, 2018, to July 15, 2020. EXPOSURES: Reduction in behavioral health care coinsurance from 50% to 20% between January 1, 2009, and January 1, 2014. MAIN OUTCOMES AND MEASURES: Total annual spending for outpatient behavioral health care visits and the percentage of beneficiaries with an annual outpatient behavioral health care visit overall, with a prescriber, and with a psychiatrist. A difference-in-difference approach was used to compare outcomes before and after the reduction in coinsurance for beneficiaries with and without cost-sharing decreases. Linear regression models with beneficiary fixed effects that adjusted for time-changing beneficiary- and area-level covariates were used to examine changes in outcomes. RESULTS: The study included 793 275 beneficiaries with SMI in 2008; 518 893 (65.4%) were younger than 65 years (mean [SD] age, 57.6 [16.1] years), 511 265 (64.4%) were female, and 552 056 (69.6%) were White. In 2008, the adjusted percentage of beneficiaries with an outpatient behavioral health care visit was 40.7% (95% CI, 40.4%-41.0%) among those eligible for the cost-sharing reduction and 44.9% (95% CI, 44.9%-45.0%) among those with free care. The mean adjusted out-of-pocket costs for outpatient behavioral health care visits decreased from $132 (95% CI, $129-$136) in 2008 to $64 (95% CI, $61-$66) in 2016 among those with reductions in cost-sharing. The adjusted percentage of beneficiaries with behavioral health care visits increased to 42.2% (95% CI, 41.9%-42.5%) in the group with a reduction in coinsurance and to 47.2% (95% CI, 47.0%-47.3%) in the group with free care. The cost-sharing reduction was not positively associated with visits (eg, relative change of −0.76 percentage points [95% CI, −1.12 to −0.40 percentage points] in the percentage of beneficiaries with outpatient behavioral health care visits in 2016 vs 2008). CONCLUSIONS AND RELEVANCE: This cohort study found that beneficiary costs for outpatient behavioral health care decreased between 2009 and 2014. There was no association between cost-sharing reductions and changes in behavioral health care visits. Low levels of use in this high-need population suggest the need for other policy efforts to address additional barriers to behavioral health care.